The Determinants of Financial Performance of Microfinance Institutions in Pakistan: The Moderating Role of Board Risk Committee - Khalid, Hafeez (UNIVERSITI MALAYSIA SARAWAK, 2025)
The performance of microfinance institutions is central to advancing financial inclusion in emerging economies but remains underexplored in Pakistan regarding the combined influence of corporate governance, financial inclusion, and credit risk. This study addresses this gap by examining how corporate governance, financial inclusion, and credit risk affect performance of microfinance institutions and the moderating role of the board risk committee. Using a balanced panel of 19 microfinance institutions from 2012 to 2021, performance is measured by return on asset, return on equity, and operational self-sufficiency. The explanatory variables include corporate governance factors (board size, board independence, female directors, audit committee), financial inclusion factors (annual percentage rate, operational efficiency), and credit risk factors (portfolio at risk, non-performing loans), with firm size and leverage as controls. The findings of panel data analysis show that strong corporate governance including larger boards, greater independence, female representation, and active audit committees significantly enhances the financial performance of microfinance institutions in Pakistan. In contrast, high annual percentage rates lower performance, while better operational efficiency improves it. Moreover, credit risk indicators such as portfolio at risk and non-performing loans negatively affect performance. Importantly, the board risk committee not only has a positive direct effect but also reduces the adverse impact of credit risk on performance. The policy implications of this study suggest for effective governance and risk oversight are critical to sustaining profitability and stability in the microfinance sector. Keywords: Corporate governance, financial inclusion, credit risk, microfinance institutions, board risk committee